The Dynamics of a Dene Struggle for Self-Determination - Smith, David M. (Anthropologica, 2022)
This paper is about the social drama occurring when the Dene of a northern Canadian community sought to attain local self determination, and Eurocanadians within the town and government officials beyond the settlement responded to their efforts. Each group found itself not merely in conflict with other groups, but enmeshed in internal symbolic paradoxes, which challenged basic images they held concerning their cultural identities. This article adds to the literature on interethnic relations in Canada, and reveals some of the subtle, even liminal, barriers to the creation of post-colonial society, encountered in the praxis of decolonialization